The influence of ICT accessibilities on learning outcomes in Cambodian public higher education institutions: The mediating role of self-efficacy - Nguon, Chanbopheak; Ali, Dhakir Abbas (Edelweiss Applied Science and Technology, 2025)
The integration of Information and Communication Technology (ICT) in education has become a key strategy to enhance teaching quality and student performance. This study explores the mediating role of self-efficacy in the relationship between ICT accessibility and learning outcomes in Cambodian public higher education. Data were collected from 326 students across three public universities using structured questionnaires. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to assess the measurement and structural models. The measurement model demonstrated strong reliability and validity (Cronbach’s α and CR > 0.90, AVE > 0.60). The structural model explained 24.4% of the variance in learning outcomes and 14.9% in self-efficacy. Findings revealed that ICT accessibility significantly influences both learning outcomes (β = 0.287, p = 0.000) and self-efficacy (β = 0.389, p = 0.000). Self-efficacy also exerted a positive effect on learning outcomes (β = 0.307, p = 0.000) and mediated the relationship between ICT accessibility and learning outcomes (β = 0.119, p = 0.000). Effect size and model fit indices confirmed the robustness of the results. The study highlights that improving ICT infrastructure must be complemented by strategies to strengthen students’ self-efficacy to optimize educational achievement.